Usability Analysis of the SIPBSI Website using the System Usability Scale as a Basis for Interface Improvement Priorities - Kieky Adrian Sarwono; Charitas Fibriani (SCOPUS ID=57192643331) (SISTEMASI, 2026)
The Information System of the Indonesian Badminton Association (SIPBSI) is a web-based system designed to manage athlete, club, and ranking data in an integrated manner. The successful implementation of such a system is determined not only by its functionality but also by its level of usability, which influences user satisfaction and acceptance. However, the usability of SIPBSI from the users’ perspective has not yet been clearly established. This study aims to evaluate the usability level of the SIPBSI website using the System Usability Scale (SUS) and to develop prioritized recommendations for interface improvement. A quantitative approach was employed, with data collected through a SUS questionnaire administered to 30 respondents who were active club coaches in Salatiga City. The research procedures included calculating the SUS score, analyzing the mean scores of individual items, and mapping the results onto usability aspects, including learnability, consistency, complexity, need for assistance, and interface clarity. The results show that the SIPBSI website achieved an average SUS score of 62. Based on SUS interpretation, this score corresponds to Grade D, with an adjective rating of “Poor” and an acceptability rating of “Marginal.” Further analysis revealed that the main usability issues were related to need for assistance (2.20), learnability (2.22), consistency (2.30), complexity (2.33), and interface clarity (2.46). These findings indicate that the usability of the system still needs improvement, as usability issues may hinder the effectiveness of data management and access in supporting PBSI operations at both regional and national levels. The redesign recommendations focus on simplifying navigation and user flows, improving interface consistency, and providing clear instructions or user assistance features. This study is expected to serve as an evaluation reference and provide practical recommendations for developers to improve the quality and usability of the SIPBSI website.